The United Nations and the Paralysis of International Justice: Critical Overview of the UN's Role in the Gaza Conflict - Ribka Levina Wibisono; Nelsen Wibisono Sutikno; Gita Venolita Valentina Gea (Bulan Sabit Merah Indonesia, 2026)
The Israel-Palestine conflict has endured for decades without a definitive resolution, resulting in catastrophic humanitarian consequences. The United Nations (UN), as the mandated guardian of peace, has undertaken numerous efforts, such as establishing the United Nations Relief and Works Agency for Palestine Refugees in the Near East (UNRWA), executing its mandates through Security Council resolutions, and proceedings before the International Court of Justice (ICJ). However, the persistence of Israel’s violence demonstrates the UN’s failure in enforcing peaceful measures and accountability for violations in Gaza. This has raised a new perspective concerning the UN’s institutional credibility and its ability to uphold the principles under the UN Charter. This paper aims to analyze the effectiveness of the UN’s role in addressing the Gaza conflict and to evaluate its actions in carrying out its resolution. Thus, the paper conducts a juridical-normative method, utilizing statutory, conceptual, and case approaches to examine the actions between both parties, the application of general principles of law, and how structural power dynamics undermine the UN’s ability to enforce and uphold justice in the Gaza conflict. The findings show that the UN’s role remains far from optimal in resolving the Gaza conflict, primarily due to the restrictive mechanisms within the organization itself that paralyze effective action. These structural and procedural limitations, such as bureaucratic constraints on its subsidiary bodies, have hindered the UN’s responsiveness towards the crisis. Consequently, the very mechanisms intended to safeguard international peace and protect human rights have instead constrained the UN’s ability to intervene effectively and alleviate the ongoing humanitarian suffering in Gaza. Therefore, this institutional amendment is essential to strengthen the UN’s decisiveness, uphold humanitarian principles, and effectively maintain peace in resolving the Gaza conflict.